Never left behind chair 2.0 - Khair, Nur Adilah; Mat Zaini, Nurul Syazwani; Yunus, Murfiqah Yasmin; M. Said, Salasiah; Tarsik, Nor Famiza (Universiti Teknologi MARA, Kedah, 2019)
Left-handed person always feel that they are being left behind when it comes to the facilities provided for the public because most of the facilities such as tables that being provided in the classroom are only suitable for the right-handed person since they are the major group in this world. So, this chair was specially designed for left-handed person. However, both right-handed person and left-handed person can use them. It gives justice to the left-handed group and comfort to the right-handed person. In other words, it was designed for everyone in this entire world. Besides, this product also can be used by handicap person because the product’s features were also being made out of their considerations. The aim of this product is to let people gain knowledge comfortably despite their condition. On top of that, an informational and knowledgeable community will be able to be produced since knowledge can be gain comfortably and easily for everyone using this chair.